Evaluation of Cystatin C for the Detection of Chronic Kidney Disease in Cats. (27th July 2016) - Ghys, L.F.E.; Paepe, D.; Lefebvre, H.P.; Reynolds, B.S.; Croubels, S.; Meyer, E.; Delanghe, J.R.; Daminet, S.
Abstract : Background: Serum cystatin C (sCysC) and urinary cystatin C (uCysC) are potential biomarkers for early detection of chronic kidney disease (CKD) in cats. An in‐depth clinical validation is required. Objectives: To evaluate CysC as a marker for CKD in cats and to compare assay performance of the turbidimetric assay (PETIA) with the previously validated nephelometric assay (PENIA). Animals: Ninety cats were included: 49 CKD and 41 healthy cats. Methods: Serum CysC and uCysC concentrations were prospectively evaluated in cats with CKD and healthy cats. Based on plasma exo‐iohexol clearance test (PexICT), sCysC was evaluated to distinguish normal, borderline, and low GFR. Sensitivity and specificity to detect PexICT < 1.7 mL/min/kg were calculated. Serum CysC results of PENIA and PETIA were correlated with GFR. Statistical analysis was performed using general linear modeling. Results: Cats with CKD had significantly higher mean ± SD sCysC (1.4 ± 0.5 mg/L) ( P < .001) and uCysC/urinary creatinine (uCr) (291 ± 411 mg/mol) ( P < .001) compared to healthy cats (sCysC 1.0 ± 0.3 and uCysC/uCr 0.32 ± 0.97). UCysC was detected in 35/49 CKD cats. R 2 values between GFR and sCysC or sCr were 0.39 and 0.71, respectively (sCysC or sCr = μ + GFR + ε). Sensitivity and specificity were 22 and 100% for sCysC and 83 and 93% for sCr. Serum CysC could not distinguish healthy from CKD cats, nor normal from borderline or low GFR, in contrast with sCr. Conclusion: Serum CysC is not a reliable marker of reduced GFR in cats and uCysC could not be detected in all CKD cats.